Assessment of Suitable Electrical Reconfiguration Method for PSC Conditions in PV Panels - S. Ramesh Prabhu, (Journal of Electronic Design Engineering, 2021)
Fluctuating solar radiation highly weakens the output power from the solar photovoltaic modules. This fluctuation act as Partial Shading Conditions (PSC) in solar power extraction. PSC is the most commonly prevailing condition among the PV arrays invoking the mismatch and power losses. To mitigate these losses, various conventional interconnection topologies have been suggested in the literature. Physical relocation of panels can be used as a practical solution to prevent such problems by altering the location of panels but not its electrical circuit. This paper presents comparative analysis of six electrical interconnection techniques for the PV modules which mitigates the effects of PSC. The aim is to reduce energy losses in photovoltaic panels operating under partial shading conditions. The techniques are evaluated through computer simulations, with the help of PSIM® software. A comparison is made between these techniques, defining which is the most suitable for each shading profile.